1984
DOI: 10.1111/j.1399-0004.1984.tb01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Two fertile Turner women in a family

Abstract: Two fertile women, mother and daughter, both presenting sex chromosomal mosaicism (45, X/46, XX/47, XXX and 45, X/46, Xr(X)) are reported. The mechanisms through which a Turner woman can eventually be fertile are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Danish researchers detected chromosome anomalies in 6 of 26 babies born from mothers with mosaic TS [17]. Similarly, a woman with a mosaic TS karyotype delivered 6 term births and only one baby was diagnosed with TS [18]. In our patients, only 2 babies from 18 term babies underwent a chromosome analysis and were found to be normal.…”
Section: Discussionsupporting
confidence: 46%
“…Danish researchers detected chromosome anomalies in 6 of 26 babies born from mothers with mosaic TS [17]. Similarly, a woman with a mosaic TS karyotype delivered 6 term births and only one baby was diagnosed with TS [18]. In our patients, only 2 babies from 18 term babies underwent a chromosome analysis and were found to be normal.…”
Section: Discussionsupporting
confidence: 46%
“…Most concern a partial deletion of Xp (Fitzgerald et al 1984). Ayuso et al (1984) explained that normal ovarian function could occur in these patients if there was a secondary cell line containing a normal X chromosome or a structural rearrangement that did not involve the "critical region". The critical region for normal ovarian function lies on the proximal part (Xcen-Xp11) of the short arm (Wyss et al 1992, Therman & Susman 1990.…”
Section: Discussionmentioning
confidence: 99%
“…The actual chromosomal anomaly was discovered by Ford (1959). Since that time, fertility has been described in women with both mosaic (Reyes et al 1976, Nielsen et al 1995, Fitzgerald et al 1984, Ayuso et al 1984, and non-mosaic Turner syndrome (Reyes et al 1976, King et al 1978, Baudier et al 1985, Varela et al 1991, including those with a structural rather than numerical X-chromosomal abnbrmality (Fryns et al 1982, Fitzgerald et al 1984, Fryns et al 1988). Premature menopause (Fitzgerald et al 1984), and an increased risk of miscarriage and abnormal offspring (Reyes et al 1979, King et al 1978 have also been reported.…”
mentioning
confidence: 99%
“…Spontaneous puberty seems to appear in 10 to 20 % of the patients with Turner syndrome, but less than 5 % of these patients have spontaneous periods [10,11]. Spontaneous pregnancy can occur in 2 to 5 % of cases, especially when the syndrome is associated with a high degree of mosaicism [12][13][14].…”
Section: Introductionmentioning
confidence: 99%